Mapping the tRNA modification landscape of Bartonella henselae Houston I and Bartonella quintana Toulouse - Quaiyum, Samia; Sun, Jingjing; Marchand, Virginie; Sun, Guangxin; Reed, Colbie J.; Motorin, Yuri; Dedon, Peter C.; Minnick, Michael F.; de Crécy-Lagard, Valérie (Frontiers in Microbiology, 2024)
Transfer RNA (tRNA) modifications play a crucial role in maintaining translational fidelity and efficiency, and they may function as regulatory elements in stress response and virulence. Despite their pivotal roles, a comprehensive mapping of tRNA modifications and their associated synthesis genes is still limited, with a predominant focus on free-living bacteria. In this study, we employed a multidisciplinary approach, incorporating comparative genomics, mass spectrometry, and nextgeneration sequencing, to predict the set of tRNA modification genes responsible for tRNA maturation in two intracellular pathogens-Bartonella henselae Houston I and Bartonella quintana Toulouse, which are causative agents of cat-scratch disease and trench fever, respectively. This analysis presented challenges, particularly because of host RNA contamination, which served as a potential source of error. However, our approach predicted 26 genes responsible for synthesizing 23 distinct tRNA modifications in B. henselae and 22 genes associated with 23 modifications in B. quintana. Notably, akin to other intracellular and symbiotic bacteria, both Bartonella species have undergone substantial reductions in tRNA modification genes, mostly by simplifying the hypermodifications present at positions 34 and 37. B. quintana exhibited the additional loss of four modifications and these were linked to examples of gene decay, providing snapshots of reductive evolution.